A novel cytochrome P450 mono‐oxygenase from Streptomyces platensis resembles activities of human drug metabolizing P450s. Issue 9 (11th July 2018) - Worsch, Anne; Eggimann, Fabian Kurt; Girhard, Marco; von Bühler, Clemens J.; Tieves, Florian; Czaja, Rico; Vogel, Andreas; Grumaz, Christian; Sohn, Kai; Lütz, Stephan; Kittelmann, Matthias; Urlacher, Vlada B.
Abstract: Cytochrome P450 mono‐oxygenases (P450) are versatile enzymes which play essential roles in C‐source assimilation, secondary metabolism, and in degradations of endo‐ and exogenous xenobiotics. In humans, several P450 isoforms constitute the largest part of phase I metabolizing enzymes and catalyze oxidation reactions which convert lipophilic xenobiotics, including drugs, to more water soluble species. Recombinant human P450s and microorganisms are applied in the pharmaceutical industry for the synthesis of drug metabolites for pharmacokinetics and toxicity studies. Compared to the membrane‐bound eukaryotic P450s, prokaryotic ones exhibit some advantageous features, such as high stability and generally easier heterologous expression. Here, we describe a novel P450 from Streptomyces platensis DSM 40041 classified as CYP107L that efficiently converts several commercial drugs of various size and properties. This P450 was identified by screening of actinobacterial strains for amodiaquine and ritonavir metabolizing activities, followed by genome sequencing and expression of the annotated S. platensis P450s in Escherichia coli . Performance of CYP107L in biotransformations of amodiaquine, ritonavir, amitriptyline, and thioridazine resembles activities of the main human metabolizing P450s, namely CYPs 3A4, 2C8, 2C19, and 2D6. For application in the pharmaceutical industry, an E. coli whole‐cell biocatalyst expressing CYP107L was developed and evaluated for preparative amodiaquine metabolite production. Abstract : In the pharmaceutical industry, drug metabolites are not only required for metabolite identification (MetID) but also as analytical reference standards as well as for pharmacokinetics and toxicity studies (DMPK). We identified a new promiscuous cytochrome P450 mono‐oxygenase from Streptomyces platensis, classified as CYP107L, that resembles the activities of the main human drug metabolizing CYPs 3A4, 2D6, 2C9, and 2C19 and developed an efficient Escherichia coli whole‐cell biocatalyst for biotransformations of selected drugs.